Hansel and Gretel - Illustrated by Ray, Marina Le (London Ladybird Books)
The classic story of a woodcutter's two lost children, who find a house in the forest made of sweets and candy that belongs to a hungry witch.
Include Color Illustrations
Keywords: Children Story